Genomic library construction of metroxylon sagu - Heng, Wei Sze (Universiti Malaysia Sarawak (UNIMAS), 2005)
Metroxy/on sagu or sago palm has been recognized as staple food for some of the indigenous society of the South East Asia population. It is an increasingly socio-economically important edible crop thus having significant commercial values. Previous researches on sago palm emphasized more on morphological, physiological and physiocbemical studies rather than genomic studies. It is crucial to have a functional genomics and proteomics reference on sago palm. Thus, the genomic library construction of Metroxy/on sagu is an important tool to facilitate the study of sago palm's functional genomics and proteomics. The genomic library construction is based on the principle of the restriction endonuclease partial digestion by using I unit of enzyme per Jlg of DNA. The concentration of BamH I is 10 Jl/JlI, 4000 U. Approximately 0.3 Jlg of BamH I-digested insert is used with every I Jlg of vector in ligating the insert into the phage. Subsequently, only 1-4 JlI of the 0.3 Jlg eluted BamH I-digested insert is used in the packaging protocol. The titering of the packaging reaction is then further proceed with the NZY agar. A total of 2.875 x 105 pfulml was formed by plating 2 JlI of the packaged phage.